THE EFFECT OF SUPPLEMENTATION OF MICROALGAE SCHIZOCHYTRIUM SP. AS A SOURCE OF DOCOSAHEXAENOIC ACID (DHA) ON DOGS WITH NATURALLY OCCURRING GINGIVITIS - Souza, Camilla Mariane Menezes; de Lima, Daniele Cristina; Bastos, Tais Silvino; Komarcheuski, Alina Stadnik; de Oliveira, Simone Gisele; Félix, Ananda Portella (Archives of Veterinary Science, 2020)
The objective of this study was to evaluate the effects of the microalgae Schizochytrium sp., as a dietary source of docosahexaenoic acid (DHA), on dogs with gingivitis. Two diets containing 0 and 0.4% of microalgae Schizochytrium sp. were offered for 30 days to 12 randomly distributed adult Beagles to determine gingivitis. Gingivitis score and area were analyzed on days 0 and 30. Prior to the analysis, the area was gently cleaned with cotton wool on the surface of the crown of the teeth. There was no change in the gingivitis score (P>0.05). However, there was a reduction (P<0.05) in the area affected by gingivitis (day 30 - day 0) in animals supplemented with 0.4% microalgae Schizochytrium sp. The addition of 0.4% dietary microalgae reduced the area of gingivitis on dogs.